Aqueous Solubility Analysis of Polycyclic aromatics and Halobenzenes: Influence of Solubility Parameter and Molar Volume - Satyanarayana, D.; Narayana Charyulu, R.; Nagavi, B.G.; Gundu Rao, P. (Asian Journal of Chemistry, 2010)
The aqueous solubility data of non-electrolytes, polycyclic aromatic compounds and halobenzenes are analysed in terms of different physico-chemical properties of the solutes. Solubility parameter and molar volume are estimated using Fedors fragmental constants, while melting point is readily available in the literature. These properties are implicated in the prediction of aqueous solubility and regression equations were obtained. Though the approach is empirical, it pelmits the estimation of aqueous solubility of untested solutes.